Open your eyes : deaf studies talking - Deaf Studies Think Tank (2002 : Gallaudet University); Bauman, H-Dirksen L., 1964- (Minneapolis : University of Minnesota Press, 2008)
This groundbreaking volume introduces readers to the key concepts and debates in deaf studies, offering perspectives on the relevance and richness of deaf ways of being in the world. In Open Your Eyes, leading and emerging scholars, the majority of whom are deaf, consider physical and cultural boundaries of deaf places and probe the complex intersections of deaf identities with gender, sexuality, disability, family, and race. Together, they explore the role of sensory perception in constructing community, redefine literacy in light of signed languages, and delve into the profound medical, social, and political dimensions of the disability label often assigned to deafness.
Talking culture and culture talking / Tom Humphries -- Colonialism and resistance / Paddy Ladd -- The deaf convert culture and its lessons for deaf theory / Frank Bechter -- Upon the formation of a visual variety of the human race / Benjamin Bahan -- Coequality and transnational studies / Joseph J. Murray -- Sound and belonging / Hilde Haualand -- On the disconstruction of (sign) language in the western tradition / H-Dirksen L. Bauman -- Turning literacy inside out / Marlon Kuntze -- Critical pedagogy and ASL videobooks / Lawrence Fleischer -- The decline of deaf clubs in the United States / Carol Padden -- Think-between / Brenda Jo Brueggemann -- Border crossings by hearing children of deaf parents / Robert Hoffmeister -- Dysconscious audism / Genie Gertz -- The burden of racism and audism / Lindsay Dunn -- Where is deaf HERstory? / Arlene Blumenthal Kelly -- Queer as deaf / MJ Bienvenu -- Do deaf people have a disability? / Harlan Lane -- Beyond culture / Douglas C. Baynton -- Postdeafness / Lennard J. Davis.
"This book was born out of the Deaf Studies Think Tank, a three-day symposium in the summer of 2002"--Pref.
Includes bibliographical references and index.
Keywords: Deaf people -- Congresses; Deaf people -- Social conditions -- Congresses; Sign language -- Congresses